Vocational education and training in ASEAN member states : current status and future development - Bai, Bin [Herausgeber]; Paryono [Herausgeber] (Springer, 2019)
"This book is the first monograph to systematically introduce readers to technical and vocational education and training in ASEAN countries. It details the current state of development and key development trends regarding technical and vocational education and training in the ten ASEAN countries. For each ASEAN country, the book addresses the history, status quo, characteristics, reform and development trends in technology and vocational education and training. The content mainly focuses on technology and vocational education and training systems, vocational qualification frameworks, technology and vocational education and training related personnel, etc. All the latest data presented here is drawn from the newest official website and research reports, accurately reflecting the development status of ASEAN countries and helping us make better forecasts regarding its future. This book offers a valuable reference guide for academic research in technology and vocational education and training. It can also be used as a textbook for postgraduate courses in technology and vocational education and training, as well as training material for various vocational education teachers and managers." (Publisher, BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; G 1.2.3.2 Anforderungen & Bedarfe; I 2.3.4 Asien; Berufsbildung; Lebenslanges Lernen; Qualifikationsbedarf; Südostasien; Brunei; Kambodscha; Indonesien; Laos; Malaysia; Myanmar; Philippinen; Singapur; Thailand; Vietnam; 2016-2020